Formative evaluation of the implementation of digital therapeutics for opioids and other substance use disorders in primary care (DIGITS trial) - Lorella Palazzo; Caitlin N. Dorsey; Jess Mogk; Tara Beatty; Deborah King; Kelsey Stefanik-Guizlo; Dustin Key; Tessa E. Matson; Mary Shea; Ryan M. Caldeiro; Angela Garza McWethy; Edwin S. Wong; et al. (Implementation Research and Practice)
Background Substance use disorders (SUDs) result in individual and societal burden. However, most individuals with SUD receive no treatment. Implementing SUD interventions in primary care could address this population's treatment needs. In the USA, reSET ® and reSET-O ® were the first prescription digital therapeutics (PDTs) for SUDs and opioid use disorder (OUD), respectively. The Digital Treatments for Substance Use Disorder (DIGITS) study tested the effectiveness of practice facilitation and health coaching strategies to support reSET and reSET-O implementation into primary care. A formative evaluation was conducted to monitor implementation, inform adaptations, and learn what promotes PDT sustainment. Method The Dynamic Sustainability Framework and the Framework for Reporting Adaptations and Modifications to Evidence-based Implementation Strategies guided the evaluation. Using rapid qualitative methods, we collected and analyzed observational fieldnotes, key informant interviews, and document sources (e.g., meeting minutes) for synthesis and dissemination to clinical partners and the study team via formative reports. We analyzed the reports to generate evaluation results. Results Twenty-four primary care clinics participated. Evaluation data included 98 observational fieldnotes, 16 interviews, and 253 document sources. We produced nine formative reports. The study encountered barriers and facilitators in each DSF domain (ecological system, practice setting, and intervention). In the ecological system, the PDT vendor enabled the study, but the COVID-19 pandemic, laws, regulations, and contracting delayed implementation. In the practice setting, staff shortages and low clinic capacity were implementation challenges, while electronic health record capabilities were both barriers and facilitators. At the intervention level, non-routine workflows, clinician burden, and low patient engagement were barriers despite clinicians’ efforts. Conclusions Digital therapeutics are promising SUD and OUD treatments, but integration into primary care requires conducive laws and regulations, organizational capacity, and patient and clinician engagement. Formative evaluation identified important lessons for future PDT implementation.